Characterization of tau positron emission tomography tracer [18F]AV‐1451 binding to postmortem tissue in Alzheimer's disease, primary tauopathies, and other dementias. Issue 11 (15th February 2016) - Sander, Kerstin; Lashley, Tammaryn; Gami, Priya; Gendron, Thibault; Lythgoe, Mark F.; Rohrer, Jonathan D.; Schott, Jonathan M.; Revesz, Tamas; Fox, Nick C.; Årstad, Erik
Abstract: Introduction: Aggregation of tau is a hallmark of many neurodegenerative diseases, and tau imaging with positron emission tomography (PET) may allow early diagnosis and treatment monitoring. We assessed binding of the PET tracer [ 18 F]AV‐1451 in a range of dementias. Methods: Phosphorimaging was used to quantify binding to postmortem brain tissue from 33 patients with different, histopathologically characterized, neurodegenerative dementias. Results: [ 18 F]AV‐1451 showed high specific binding in cases with Alzheimer's disease (AD), moderate binding in Pick's disease and frontotemporal dementia with parkinsonism‐17, and low but displaceable binding in corticobasal degeneration, progressive supranuclear palsy, non–tau proteinopathies, and in controls without pathology. Tracer binding did not correlate with tau load within disease groups. Discussion: [ 18 F]AV‐1451 binds to tau in AD, and some other tauopathies. However, evidence for a non–tau binding site and lack of correlation between tracer binding and antibody staining suggest that reliable quantification of tau load with this tracer is problematic.